Antarctica and the Humanities
XXV, 312 p. 15 illus., 4 illus. in color.
Keywords: The continent for science is also a continent for the humanities. Despite having no indigenous human population, Antarctica has been imagined in powerful, innovative, and sometimes disturbing ways that reflect politics and culture much further north. Antarctica has become an important source of data for natural scientists working to understand global climate change. As this book shows, the tools of literary studies, history, archaeology, and more, can likewise produce important insights into the nature of the modern world and humanity more broadly. .